Simulation Of Mechanical Stress On A Solution-Annealed 15-15Ti Steel Using ABAQUS CAE Program - Putra Oktavianto; Anik Purwaningsih; Muksin Aji Setiawan; Airin Hijrah Handayani; Asril Pramutadi Andi Mustari; Abdul Waris (BRIN Publishing (Penerbit BRIN), 2024)
In addressing the problem of Ti steel (15-15Ti) proposed as the main candidate material for the manufacture of coatings and fuel wrappers for liquid LBE-cooled fast reactors at high temperatures related to material degradation, such as liquid metal embrittlement (LME) and liquid metal corrosion (LMC), Gong et al. conducted research related to the creep failure behavior of solution-annealed 15-15Ti steel exposed to LBE at temperatures of 550 and 600oC using a creep test facility. However, in this study, testing the mechanical properties of 15-15Ti steel through tensile testing was not really discussed, even though the mechanical properties of a material are one of the most important things in determining structural design. The mechanical properties obtained from previous research were then simulated using ABAQUS CAE software to determine the stress distribution profile (initial and final) and the mechanical stress-strain performance used to understand more about the 15–15Ti material. From the simulation results, it was found that the peak force received by the specimen for a strain rate of 1.1 x 10-5s-1 was 6.0 kN, while for a strain rate of 5 x 10-5s-1, it was 6.2 kN. This means that the specimen used cannot accept a force greater than the peak force value. A stress-strain difference graph was also obtained in the experimental results, with simulation results showing a decrease in the value of the fracture point. This is because the mesh setting in the simulation is not close to a more detailed value.